Preparation method of water-based inorganic coating with fireproof function

By applying an aqueous inorganic coating prepared from components such as water glass, aluminum hydroxide, magnesium hydroxide and zinc borate on an electronic jacquard machine, the problem of insufficient protection performance in the case of fire is solved, and the fire resistance and heat are significantly improved Stability, ensure the safety and stability of the equipment in high temperature environments.

CN119242086APending Publication Date: 2025-01-03SHAOXING YANCAI NEW BUILDING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507397.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing electronic jacquard machines are flammable and lack protection mechanisms during textile processing, which leads to damage during fire and damage to the equipment when extinguishing the fire, with poor protection performance and low stability.

Method used

Using a preparation method of a water-based inorganic coating with fire-resistant function, by mixing water glass with deionized water, adding components such as aluminum hydroxide, magnesium hydroxide and zinc borate, combining dispersant and defoaming agent, and accurately stirring and grinding process to prepare coatings with excellent fire resistance.

Benefits of technology

Significantly improve fire resistance, delay flame propagation, increase self-extinguishing time, improve the solid content, fineness and thermal stability of the paint, enhance the coating effect and adhesion of the paint, ensure stability in high temperature environments, and reduce environmental pollution .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242086A_ABST
    Figure CN119242086A_ABST
Patent Text Reader

Abstract

A preparation method of a water-based inorganic coating with a fireproof function belongs to the technical field of material science, the prepared water-based inorganic coating has an excellent fireproof function through an accurate formula and process, flame propagation can be effectively delayed, the self-extinguishing time is prolonged, and more reliable guarantee is provided for life and property safety. The solid content, fineness, viscosity and other physical properties of the coating can be accurately controlled, so that the coating can better adapt to different application scenes and construction requirements, the coating effect and adhesive force of the coating are improved, the coating has higher initial decomposition temperature, maximum weight loss rate temperature and glass transition temperature due to the synergistic effect of the formula and the process, and the coating can be applied to the construction industry. The coating can be kept stable in a high-temperature environment, the service life of the coating is prolonged, detailed formulas and algorithms of the stirring speed, the stirring time, the grinding time and the like are introduced, technological parameters of the whole preparation process are more accurate and controllable, and personal errors are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and technology, and specifically relates to a method for preparing a water-based inorganic coating with fireproof function. Background Art

[0002] In the field of textiles, fabrics are usually woven from warp and weft. On the loom, the warp must be divided into two layers according to a certain rule, forming a channel for the weft to pass through, that is, the warp opening. After the weft is introduced into the opening, the two layers of warp are alternated up and down according to the fabric organization method to form a new warp opening. This is repeated to complete the weaving process of the fabric. The formation of the warp opening is completed by the warp opening selection mechanism, which is the most core step in textile technology, but most of the existing jacquard machines still have the following problems;

[0003] At present, most of the existing electronic jacquard machines are supported by an iron frame, and the jacquard machines are welded on the frame, wherein the frame is used to support the jacquard machine body. Most electronic jacquard machines are not provided with a protective mechanism to protect the mechanical parts of the jacquard machine body, resulting in the existing jacquard machines having no protection against external interference during operation. For example, jacquard machines are mostly used in textile processing factories, and most textile items are flammable. If a fire occurs in the factory, the fire may burn the jacquard machine and the jacquard machine may be damaged. In addition, the powder and water sprayed during the fire extinguishing may damage the jacquard machine. Therefore, most of the existing jacquard machines have poor protection performance, are easily affected by external interference, and have low stability. Summary of the invention

[0004] The present invention mainly solves the technical problems existing in the above-mentioned prior art and provides a method for preparing a water-based inorganic coating with fireproof function.

[0005] The above technical problem of the present invention is mainly solved by the following technical solution: A method for preparing a water-based inorganic coating with fire retardant function, comprising the following steps:

[0006] S1: Mix water glass with deionized water in a weight ratio of 1:(0.8-1.2), stir evenly, and obtain solution A. The stirring speed calculation formula is: V=K1×(M1 / M2), where V is the stirring speed (unit: revolutions / minute), K1 is the stirring speed coefficient (value 100-150), M1 is the weight of water glass (unit: grams), and M2 is the weight of deionized water (unit: grams). At the same time, the stirring time T1=K2×log(M1+M2), where T1 is the stirring time (unit: minutes), and K2 is the time coefficient (value 10-15);

[0007] S2: According to the weight parts, add 20-30 parts of aluminum hydroxide, 10-15 parts of magnesium hydroxide, and 5-10 parts of zinc borate to solution A, and stir at a speed of 500-800 rpm for 30-60 minutes. Stirring speed V2 = K3×(W1+W2+W3), where V2 is the stirring speed (unit: rpm), K3 is the speed adjustment coefficient (value 15-25), W1 is the weight of aluminum hydroxide (unit: gram), W2 is the weight of magnesium hydroxide (unit: gram), and W3 is the weight of zinc borate (unit: gram). Stirring time T2 = K4×(W1×W2×W3)^0.5, where T2 is the stirring time (unit: minute), and K4 is the time adjustment coefficient (value 0.8-1.2). Obtain mixture B;

[0008] S3: Add 3-5 parts of dispersant and 2-4 parts of defoamer to mixture B, and stir at 300-500 rpm for 15-30 minutes. Stirring speed V3 = K5 × (D1 + D2), where V3 is the stirring speed (unit: rpm), K5 is the speed adjustment coefficient (value 80-120), D1 is the weight of the dispersant (unit: gram), and D2 is the weight of the defoamer (unit: gram). Stirring time T3 = K6 × (D1 / D2)^2, where T3 is the stirring time (unit: minute), and K6 is the time parameter (value 8-12), to obtain mixture C.

[0009] Preferably, in step S1, the optimal weight ratio of water glass to deionized water is 1:1, at which time the stirring speed coefficient K1 takes a value of 120 and the time coefficient K2 takes a value of 12.

[0010] Preferably, in step S2, when the weights of aluminum hydroxide, magnesium hydroxide and zinc borate are 25 parts, 12 parts and 8 parts respectively, the stirring speed coefficient K3 is 20 and the time adjustment coefficient K4 is 1.

[0011] Preferably, in step S3, when the dispersant is 4 parts and the defoaming agent is 3 parts, the speed adjustment coefficient K5 takes a value of 100 and the time parameter K6 takes a value of 10.

[0012] Preferably, the dispersant is a sodium polyacrylate dispersant.

[0013] Preferably, the defoamer is a silicone defoamer.

[0014] Preferably, in step S4, grinding is performed using a sand mill, the grinding medium is zirconia beads, the diameter of the zirconia beads is 0.8-1.2 mm, and the filling rate is 70-80%. Grinding efficiency E=K8×(D×F) / (L×P), where E is the grinding efficiency (unit: g / min), K8 is the grinding efficiency coefficient (value 5-10), D is the diameter of the zirconia beads (unit: mm), F is the fineness requirement (unit: micron), L is the filling rate of the zirconia beads (unit: %), and P is the viscosity of the mixture C (unit: Pa·s).

[0015] Preferably, when the diameter of the zirconia beads is 1 mm and the filling rate is 75%, the grinding efficiency coefficient K8 takes a value of 8.

[0016] Preferably, the optimal weight ratio of the aluminum hydroxide, magnesium hydroxide and zinc borate is 2:1:0.5.

[0017] Preferably, the solid content of the water-based inorganic coating is 50-60%, and the solid content calculation formula is: G = (M4 / M5) × 100%, wherein G is the solid content (unit: %), M4 is the solid component weight (unit: gram), and M5 is the total weight of the coating (unit: gram).

[0018] The present invention has the beneficial effects:

[0019] 1. Significantly improve fire resistance: Through precise formula and process, the water-based inorganic coating prepared has excellent fire resistance, can effectively delay the spread of flames, increase self-extinguishing time, and provide more reliable protection for life and property safety.

[0020] Second, optimize physical properties: The physical properties of the coating, such as solid content, fineness and viscosity, can be precisely controlled, so that it can better adapt to different application scenarios and construction requirements, and improve the coating effect and adhesion.

[0021] 3. Enhanced thermal stability: The synergistic effect of formula and process makes the coating have a higher initial decomposition temperature, maximum weight loss rate temperature and glass transition temperature, which can remain stable in high temperature environment and extend the service life of the coating.

[0022] Fourth, the process parameters are quantifiable: Detailed formulas and algorithms such as stirring speed, stirring time and grinding time are introduced to make the process parameters of the entire preparation process more precise and controllable, reduce human errors, and improve product consistency and stability.

[0023] 5. Flexible selection of raw materials: The proportion of each component can be flexibly adjusted according to actual needs to meet different cost and performance requirements while ensuring fire resistance.

[0024] 6. Environmentally friendly: Water-based inorganic coatings themselves have the characteristics of low volatile organic compound (VOC) emissions, coupled with precise preparation technology, further reducing pollution to the environment.

[0025] 7. Combination of innovation and practicality: This creative preparation method provides new ideas and solutions for the field of fire retardant coatings and has high practical value and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a structural schematic diagram of the overall side view of the device of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further specifically described below through embodiments and in conjunction with the accompanying drawings.

[0028] Water-based inorganic coatings with fireproofing function have important application value in the fields of construction, industry, etc. The present invention provides an innovative preparation method, which aims to obtain a fireproof coating with excellent performance by precisely controlling the proportion of each component and process parameters. The specific implementation process of the preparation method will be introduced in detail below, and its effect will be demonstrated through multiple examples and verification experiments.

[0029] Experimental materials: water glass, deionized water, aluminum hydroxide, magnesium hydroxide, zinc borate, polyacrylic acid sodium salt dispersant, silicone defoamer;

[0030] Experimental equipment: electronic balance (accuracy 0.01g), stirrer (adjustable speed), sand mill, particle size analyzer, oven, thermogravimetric analyzer (TGA), differential scanning calorimeter (DSC).

[0031] Embodiment 1:

[0032] S1: Weigh 100 g of water glass, and according to the weight ratio of water glass to deionized water of 1:0.8, measure 80 g of deionized water, stir at a speed according to the formula V=100×(100 / 80)=125 rpm, stir for a time of T1=10×log(100+80)≈29 minutes, and stir to obtain solution A;

[0033] S2: Weigh 20 g aluminum hydroxide, 10 g magnesium hydroxide, and 5 g zinc borate, with a stirring speed of V2 = 15 × (20 + 10 + 5) = 525 rpm and a stirring time of T2 = 0.8 × (20 × 10 × 5) ^ 0.5 ≈ 40 minutes, add to solution A and stir evenly to obtain a mixture B;

[0034] S3: Add 3 g of polyacrylic acid sodium salt dispersant and 2 g of silicone defoamer, stirring at a speed of V3 = 80 × (3 + 2) = 400 rpm, stirring for a time of T3 = 8 × (3 / 2)^2 = 18 minutes, and stir to obtain a mixture C;

[0035] S4: Grind the mixture C using a sand mill to control the fineness to 20 microns. Grinding time T4 = 0.05 × 20^2 = 20 minutes.

[0036] Embodiment 2:

[0037] S1: Weigh 100 g of water glass, and according to the weight ratio of water glass to deionized water of 1:1, measure 100 g of deionized water, stir at a speed of V = 120 × (100 / 100) = 120 rpm, stir for a time of T1 = 12 × log (100 + 100) ≈ 34 minutes, and stir to obtain a solution A;

[0038] S2: Weigh 25 g aluminum hydroxide, 12 g magnesium hydroxide, and 7 g zinc borate, with a stirring speed of V2 = 20 × (25 + 12 + 7) = 800 rpm and a stirring time of T2 = 1 × (25 × 12 × 7) ^ 0.5 ≈ 47 minutes, add to solution A and stir evenly to obtain a mixture B;

[0039] S3: Add 4 g of polyacrylic acid sodium salt dispersant and 3 g of silicone defoamer, stir at a speed of V3 = 100 × (4 + 3) = 700 rpm, stir for a time of T3 = 10 × (4 / 3) ^ 2 ≈ 18 minutes, and stir to obtain a mixture C;

[0040] S4: Grind the mixture C using a sand mill to control the fineness to 25 microns. Grinding time T4 = 0.08 × 25^2 = 50 minutes.

[0041] Embodiment 3:

[0042] S1: Weigh 100 g of water glass, and according to the weight ratio of water glass to deionized water of 1:1.2, measure 120 g of deionized water, stir at a speed of V = 150 × (100 / 120) ≈ 125 rpm, stir for a time of T1 = 15 × log (100 + 120) ≈ 40 min, and stir to obtain a solution A;

[0043] S2: Weigh 30 g aluminum hydroxide, 15 g magnesium hydroxide, and 10 g zinc borate, with a stirring speed of V2 = 25 × (30 + 15 + 10) = 1125 rpm and a stirring time of T2 = 1.2 × (30 × 15 × 10) ^ 0.5 ≈ 58 minutes, add to solution A and stir evenly to obtain a mixture B;

[0044] S3: Add 5 g of polyacrylic acid sodium salt dispersant and 4 g of silicone defoamer, stirring speed V3 = 120 × (5 + 4) = 1080 rpm, stirring time T3 = 12 × (5 / 4) ^ 2 = 22.5 minutes, and stir to obtain mixture C;

[0045] S4: Grind the mixture C using a sand mill to control the fineness to 30 microns. Grinding time T4 = 0.1 × 30^2 = 90 minutes.

[0046] Verification experiment:

[0047] 1. Use the vertical combustion method to test the fire resistance of the prepared water-based inorganic coating. Record the parameters such as ignition time, flame propagation speed, self-extinguishing time, etc. The experimental results are as follows:

[0048]

[0049] 2. Test the solid content, fineness, viscosity and other physical properties of the coating. Solid content: calculated according to the formula G = (M4 / M5) × 100%, where M4 is the solid mass after drying, M5 is the mass of the coating sample, fineness: measured using a particle size analyzer, viscosity: measured using a rotational viscometer, experimental results:

[0050]

[0051] 3. Use thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) to analyze the thermal stability of the coating. The experimental results are as follows:

[0052]

[0053] By analyzing the test results of the three embodiments, it can be seen that in terms of fireproof performance, embodiment 3 performs best, with a longer ignition time, a slower flame propagation speed, and a shorter self-extinguishing time, indicating that it has the best fireproof effect. In terms of physical properties, with the increase in the proportion of each component and the optimization of process parameters, embodiment 3 has a higher solid content, a larger fineness, and an increased viscosity. In terms of thermal stability, the initial decomposition temperature, the maximum weight loss rate temperature, and the glass transition temperature of embodiment 3 are all higher, indicating that it has the best thermal stability. Comprehensively considered, the formula and process parameters of embodiment 3 can prepare a water-based inorganic coating with excellent performance and fireproof function.

[0054] The method for preparing a water-based inorganic coating with a fireproof function of the present invention successfully prepares a water-based inorganic coating with excellent fireproof performance, good physical properties and high thermal stability by accurately controlling the proportion of each component and process parameters. The results of multiple embodiments and verification experiments show that the method has high feasibility and practicality, and provides a new idea and method for the preparation of fireproof coatings.

[0055] Through precise formula and process, the prepared waterborne inorganic coating has excellent fireproof function, can effectively delay the spread of flame, increase the self-extinguishing time, and provide more reliable protection for the safety of life and property. The solid content, fineness and viscosity of the coating can be precisely controlled to enable it to better adapt to different application scenarios and construction requirements, improve the coating effect and adhesion of the coating, and the synergistic effect of the formula and process makes the coating have a higher initial decomposition temperature, maximum weight loss rate temperature and glass transition temperature, and can remain stable in a high temperature environment, extending the service life of the coating. Detailed formulas and algorithms such as stirring speed, stirring time and grinding time are introduced to make the process parameters of the entire preparation process more precise and controllable, reduce human errors, and improve the consistency and stability of the product. The proportion of each component can be flexibly adjusted according to actual needs to meet different cost and performance requirements while ensuring fireproof performance. The waterborne inorganic coating itself has the characteristics of low volatile organic compound (VOC) emissions, coupled with precise preparation technology, further reducing pollution to the environment. This creative preparation method provides new ideas and solutions for the field of fire retardant coatings and has high practical value and application prospects.

[0056] In the process of implementing the method for preparing the water-based inorganic coating with fireproof function of the present invention, we fully consider the synergy and optimization of each link;

[0057] First, for the selection of raw materials, we strictly screen high-quality water glass, aluminum hydroxide, magnesium hydroxide, zinc borate, etc. to ensure the stability of the basic performance of the coating. In terms of material pretreatment, the raw materials are dried and the particle size is screened in advance to remove impurities and oversized particles that may affect the reaction, creating good conditions for subsequent reactions;

[0058] Temperature control during the mixing process is also crucial. Appropriate temperature helps the ingredients to mix and react fully, avoiding incomplete reactions or side reactions caused by improper temperature. At the same time, according to different reaction stages, the intensity and method of mixing should be adjusted in time. For example, higher intensity mixing should be used in the initial mixing stage to promote rapid and uniform mixing, while the intensity of mixing should be appropriately reduced when adding sensitive ingredients to prevent damage to the ingredients caused by excessive shearing.

[0059] In the grinding stage, in addition to controlling the fineness to meet the specified requirements, attention is also paid to the heat accumulation and material fluidity during the grinding process. Effective cooling measures are adopted to prevent overheating from affecting the performance of the coating, and the filling amount and distribution of the grinding media are adjusted to ensure the efficiency and uniformity of the grinding;

[0060] In the storage and packaging of the paint after preparation, we select appropriate containers and packaging materials to prevent the paint from reacting with the external environment or being contaminated. At the same time, the temperature, humidity and ventilation conditions of the storage environment are strictly controlled to ensure the stability of the paint performance during storage;

[0061] In addition, the entire preparation process strictly follows safe operating procedures and fully evaluates and prevents possible dangerous factors. The staff is equipped with necessary protective equipment, and the equipment is regularly maintained and calibrated to ensure that the preparation work is carried out safely and efficiently;

[0062] Through careful control and optimization of each of the above links, we are able to stably and efficiently prepare water-based inorganic coatings with excellent fire retardant properties to meet the market's growing demand and high standards for fire retardant coatings.

[0063] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention should be considered to belong to the protection scope of the present invention.

Claims

1. A method for preparing a water-based inorganic coating having a fire retardant function, characterized in that: The following steps are involved: S1: Mix water glass with deionized water in a weight ratio of 1:0.8-1.2, stir evenly, and obtain solution A. The stirring speed calculation formula is: V=K1×(M1 / M2), where V is the stirring speed, K1 is the stirring speed coefficient, M1 is the weight of water glass, and M2 is the weight of deionized water. At the same time, the stirring time T1=K2×log(M1+M2), where T1 is the stirring time and K2 is the time coefficient; S2: According to the weight parts, 20-30 parts of aluminum hydroxide, 10-15 parts of magnesium hydroxide, and 5-10 parts of zinc borate are added to solution A, and stirred at a speed of 500-800 rpm for 30-60 minutes, the stirring speed V2=K3×(W1+W2+W3), wherein V2 is the stirring speed, K3 is the speed adjustment coefficient, W1 is the weight of aluminum hydroxide, W2 is the weight of magnesium hydroxide, W3 is the weight of zinc borate, and the stirring time T2=K4×(W1×W2×W3)^0.5, wherein T2 is the stirring time, and K4 is the time adjustment coefficient, to obtain a mixture B; S3: Add 3-5 parts of dispersant and 2-4 parts of defoamer to mixture B, stir at 300-500 rpm for 15-30 minutes, stirring speed V3=K5×(D1+D2), wherein V3 is the stirring speed, K5 is the speed adjustment coefficient, D1 is the weight of the dispersant, D2 is the weight of the defoamer, stirring time T3=K6×(D1 / D2)^2, wherein T3 is the stirring time, and K6 is the time parameter, to obtain mixture C.

2. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 1, characterized in that: In S1, the optimal weight ratio of water glass to deionized water is 1:1, at which time the stirring speed coefficient K1 takes a value of 120 and the time coefficient K2 takes a value of 12.

3. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 2, characterized in that: In S2, when the weights of aluminum hydroxide, magnesium hydroxide and zinc borate are 25 parts, 12 parts and 8 parts respectively, the stirring speed coefficient K3 is 20 and the time adjustment coefficient K4 is 1.

4. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 3, characterized in that: In S3, when the dispersant is 4 parts and the defoamer is 3 parts, the speed adjustment coefficient K5 takes a value of 100 and the time parameter K6 takes a value of 10.

5. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 4, characterized in that: The dispersant is a sodium polyacrylic acid dispersant.

6. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 4, characterized in that: The defoamer is an organosilicon defoamer.

7. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 6, characterized in that: In S4, grinding is performed using a sand mill, the grinding medium is zirconia beads, the diameter of the zirconia beads is 0.8-1.2 mm, and the filling rate is 70-80%. Grinding efficiency E = K8×(D×F) / (L×P), where E is the grinding efficiency, K8 is the grinding efficiency coefficient, D is the diameter of the zirconia beads, F is the fineness requirement, L is the filling rate of the zirconia beads, and P is the viscosity of the mixture C.

8. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 1, characterized in that: When the diameter of the zirconia beads is 1 mm and the filling rate is 75%, the grinding efficiency coefficient K8 is 8.

9. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 8, characterized in that: The optimal weight ratio of the aluminum hydroxide, magnesium hydroxide and zinc borate is 2:1:0.

5.

10. A method for preparing a water-based inorganic coating having a fire retardant function as claimed in claim 9, characterized in that: The solid content of the water-based inorganic coating is 50-60%, and the solid content calculation formula is: G=(M4 / M5)×100%, wherein G is the solid content, M4 is the weight of the solid component, and M5 is the total weight of the coating.

Citation Information

Patent Citations

  • Environment-friendly light reflecting waterproof and fireproof colored coating for tunnels and preparation method

    CN105294046A

  • Novel inorganic intumescent steel structure fireproof coating and preparation method thereof

    CN109651856A